Pendekatan Kontekstual dalam Meningkatkan Berpikir Kritis Siswa di SMAN 1 Donorojo - Suramto Suramto; Budiyanto Budiyanto; Mujiyanto Mujiyanto (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to determine the extent to which the contextual approach influences students' critical thinking skills. The method used in this study is a correlational approach, which is an approach that aims to identify the influence between one or more variables in a group of subjects. The subjects in this study were 52 Buddhist students at SMA Negeri 1 Donorojo. The results of data analysis show that there is a significant influence between the contextual approach and students' critical thinking skills. This is evidenced by the regression coefficient value of 0.569, which indicates that students' critical thinking skills are influenced by the contextual approach. The simple linear regression equation obtained is Y = 97.261 + 0.569X.